UK national minimum wage and labor market outcomes of young workers - Jan Fidrmuc; J. D. Tena (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The UK national minimum wage (NMW) is age-specific with the most important threshold at the age of 22 (lowered to 21 from 2010 onwards) when workers become eligible for the adult rate. The authors estimate the impact of this threshold on employment by means of a regression discontinuity analysis. Because this threshold is known in advance, they investigate the presence of discontinuities in both the level and the slope of employment probabilities at different ages around the threshold. Their results indicate that turning 22 does not significantly change the employment probability. However, they find a significant change in the slope of the probability of being employed around one year before, suggesting a smooth deterioration of employment probability before turning 22 rather than a sudden change at a particular age. This finding is confirmed by a difference-in-difference analysis. However, no such effect can be found during the period preceding the introduction of the NMW.
Keywords: J21; J23; 330; minimum wage; employment; young workers; regression discontinuity design